Pemanfaatan tandan kosong kelapa sawit sisa jamur merang (Volvariella volvacea)(TKSJ) sebagai pupuk organik pada pembibitan kelapa sawit Utilization of spent mushroom (Volvariella volvacea) media derived from empty fruit bunches of oil palm (SMEB) as organic fertilizer on oil palm seedling - Happy WIDIASTUTI; . TRI-PANJI (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2007)
SummaryThe utilization of lignocellulolitic emptyfruit-bunches of oil-palm (EFBOP) material asstraw mushroom (Volvariella volvacea) mediacould produce short chain organic carbon andnutrients which may be available for growth ofplant. This research was aimed to determine theeffect of spent mushroom media amendmentderived from empty fruit bunches of oil palm(SMEB) as organic fertilizer on the growth andnutrient uptake of oil palm seedling. Theexperiment was conducted at greenhouse usingacid soil. Oil palm seedling was grown in 60 x 50cm polybags. The experiment was carried out toexamine 20 treatments i.e. combinations of fourlevel of SMEB (0, 25%, 50%, and 75% w/w) andfive dosages of conventional fertilizer (0, 25%,50%, 75%, and 100%) recommended dosages.The experiment was conducted using completerandomized design with factorial type. Theresearch showed that the amendment of SMEB atthe level of 25% could increase the height ofseedling, fresh weight of root, stem, and seedlingsas well as dry weight of oil palm stem. However,for leaf dry weight, a higher addition of SMEB upto 50% was needed. Fertilizing at 25% ofrecommended dosage could increase the seedlingheight, fresh weight of stem and leaf while forseedling fresh weight and leaf number, higheraddition of fertilizer up to 50% was needed.Significantly higher uptake of K and Mg wasobserved on the amendment of 75% of SMEB.The higher addition of SMEB (up to 75% w/w)did not decrease any growth parameters andnutrient uptake. However, the addition of 100%of recommended chemical fertilizer tended todecrease various growth parameters and uptakeof N, P, K, and Mg of oil palm seedling.RingkasanPenggunaan bahan lignoselulosa sebagaimedium jamur merang (Volvariella volvacea)diketahui dapat menghasilkan senyawa karbonrantai pendek demikian pula hara tersedia,sehingga diduga bahan ini dapat digunakansebagai pupuk organik untuk tanaman. Penelitiandilakukan untuk mengetahui pengaruh pemberiantandan kosong kelapa sawit (TKKS) sisa mediumjamur merang (TKSJ) terhadap pertumbuhan danserapan hara bibit kelapa sawit. Percobaandilakukan di rumah kaca menggunakan tanahbereaksi masam. TKKS sisa medium jamurmerang (TKSJ) sesuai dosis perlakuan dicampurdengan tanah dan selanjutnya bibit kelapa sawitditanam di polibag berukuran 60 x 50 cm.Percobaan dilakukan untuk menguji 20 perlakuanyang merupakan kombinasi empat tingkat TKSJ(0, 25%, 50% dan 75% b/b) dan lima dosis pupukkonvensional (0, 25%, 50%, 75% dan 100%)dosis rekomendasi. Percobaan dilakukan meng-gunakan rancangan acak lengkap dengan polafaktorial. Hasil percobaan menunjukkan bahwapemberian TKSJ pada tingkat 25% dapatmeningkatkan tinggi bibit, bobot basah akar,batang, dan bibit serta bobot kering batangkelapa sawit. Namun, untuk peubah bobot keringdaun diperlukan pemberian TKSJ yang lebihtinggi yaitu 50%. Pemupukan pada dosis 25%rekomendasi meningkatkan tinggi, bobot basahbatang dan daun sedangkan untuk jumlah daundan bobot basah bibit diperlukan dosis pupuk50%. Serapan hara K dan Mg nyata lebih tinggipada pemberian 75% TKSJ. Pemberian TKSJpada jumlah yang tinggi (hingga 75% b/b) tidakmenyebabkan penurunan berbagai peubah per-tumbuhan dan serapan hara, namun pemberianpupuk 100% rekomendasi cenderung menurun-kan berbagai peubah pertumbuhan dan serapanhara N, P, K, dan Mg bibit kelapa sawit.